2010
DOI: 10.1021/pr100395s
|View full text |Cite
|
Sign up to set email alerts
|

Serum Degradome Markers for the Detection of Breast Cancer

Abstract: Many proteins have been proposed as potential biomarkers for breast cancer. Yet, validation of their discriminative value using quantitative methods has scarcely been performed. In this study, we investigated the discriminative value of six peptides that were previously proposed to be generated by breast cancer specific exoproteases: bradykinin, des-Arg(9)-bradykinin, Hyp(3)-bradykinin, and fragments of fibrinogen alpha-chain (Fib-alpha ([605-629])), complement component 4a (C4a ([1337-1350])), and interalpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…It may be a reliable surrogate tissue for analysis of physiologic or pathologic processes such as cancer. Some studies have addressed the potential of proteomic research to provide serum biomarkers that differentiate breast cancer from benign healthy controls (14)(15)(16)(17)(18)(19). Our results compare well with previously reports by us and others, indicating high sensitivity and specificity when an MS profiling method is used for detecting breast cancer in readily accessible body fluids (20).…”
Section: Discussionsupporting
confidence: 89%
“…It may be a reliable surrogate tissue for analysis of physiologic or pathologic processes such as cancer. Some studies have addressed the potential of proteomic research to provide serum biomarkers that differentiate breast cancer from benign healthy controls (14)(15)(16)(17)(18)(19). Our results compare well with previously reports by us and others, indicating high sensitivity and specificity when an MS profiling method is used for detecting breast cancer in readily accessible body fluids (20).…”
Section: Discussionsupporting
confidence: 89%
“…ITIH4, a protein secreted by the liver in times of trauma and involved in the acute-phase response, was shown to have a downward trend as the amount of n-3 fatty acids increased in the dietary groups. In serum from breast cancer patients it was shown that this protein as peptide fragments was upregulated in comparison to healthy controls (46,47). ITIH4 has also proposed to be cleaved by plasma kallikrein in cancers such as ovarian and breast (47,48) which could possibly explain the bands seen at 120 kDa (data not shown) and 100 kDa.…”
Section: Discussionmentioning
confidence: 92%
“…However, in later studies, the increase in cancer cases of the 8.1 kDa marker was not found to be noteworthy, and the 8.9 kDa marker was reported to have decreased in metastatic recurrences (39). Additionally, the ITIH4 (4.3 kDa) fragment has been found to be increased in cancer cases (40,41). Thus, the value of these three biomarkers in the diagnosis of breast cancer remains controversial.…”
Section: Diagnostic Marker Protein Profiling Studiesmentioning
confidence: 98%